Bottlenecks Identification in Software Development Process: A Quali-Quantitative Approach - Ribeiro, Sildenir A. Ribeiro; Schmitz, Eber A. Schmitz (Teste; 2018: IHC_21, 2018)
This paper presents the quali-quantitative results of a study on the identification of bottlenecks in the software development process. The research was developed in an environment learning of Software Engineering and had the collaboration of students of the Department of Computer Science (DCC) of the Federal University of Rio de Janeiro (UFRJ). The main objective of the research is to verify the existence of productive bottlenecks in Software Development Process (SDP), typify them and if possible to promote treatments to solve the impacts in the process and in the software product. For this, three experimental rounds were carried out and three different domains were applied. Each round had deferential teams working in the same domain. The experiments also involved the Unified Process (UP) to guiding the SDP and the Theory of Constraints (TOC) to identify and treat the restrictive elements found in the productive process. As results, the work presents a set of qualitative constraints subdivided into two groups: (1) Behavioral Constraints (BC), and (2) Technical Constraints (TC). The identification of these qualitative constraints allowed quantitative bottlenecks to be detected. The research also showed that bottlenecks are associated with certain tasks performed in the software development environment within a given domain. In general, these tasks are consuming resources, such as effort, time and human resources. This fact leads to the software product to a low quality due to the lack of completeness and correctness of the artifacts delivered to the end of the productive process.